Fecal Microbiome and Metabolomic Profiles of Mixed-Fed Infants Are More Similar to Formula-Fed than Breastfed Infants - Mei Wang; Negin Valizadegan; Christopher J. Fields; Sharon M. Donovan (Microorganisms)
Many infants consume both human milk and infant formula (mixed-fed); however, few studies have investigated how mixed feeding affects the gut microbiome composition and metabolic profiles compared to exclusive breastfeeding or formula feeding. Herein, how delivery mode and early nutrition affect the microbiome and metabolome of 6-week-old infants in the STRONG Kids2 cohort was investigated. Fecal samples were collected from exclusively breastfed (BF; n = 25), formula-fed (FF; n = 25) or mixed-fed (MF; n = 25) participants. Within each feeding group, infants were either delivered vaginally (VD; n = 13) or by Cesarean section (CS; n = 12). Feeding mode affects the fecal microbiome diversity, composition, and functional potential, as well as metabolomic profiles regardless of delivery mode. Alpha and beta diversity of MF differed from that of BF (p < 0.05) but were comparable to FF infants. Functional analyses have shown 117 potential metabolic pathways differed between BF and FF, 112 between BF and MF, and 8 between MF and FF infants (p < 0.05, q < 0.10). Fecal metabolomic profiles of MF and FF clustered together and separated from BF infants. In total, 543 metabolites differed between BF and FF, 517 between BF and MF, and 3 between MF and FF (p < 0.05, q < 0.10). Delivery mode affected overall microbial composition (p = 0.022) at the genus level and 24 potential functional pathways, with 16 pathways being higher in VD than CS infants (p < 0.05, q < 0.10). Metabolomic analysis identified 47 differential metabolites between CS and VD, with 39 being lower in CS than VD (p < 0.05, q < 0.10). In summary, fecal microbiota composition and function and metabolite profiles of 6-week-old MF infants are closer to FF than BF infants.